PERENCANAAN STRUKTUR GEDUNG RADIOTERAPY DAN ONKOLOGY CENTRE RSUP Dr. KARIADI SEMARANG - Tintus Triubekti; Anindita Hapsari; Himawan Indarto; Muhrozi Muhrozi (Jurnal Karya Teknik Sipil, 2016)
Structural design of buildings Hospital Radiotherapy and Oncology Centre of Public Hospital Dr. Kariadi Semarang, refers to three standards: (1) minimum loads for buildings (SNI 1727-2013), (2) Earthquake resistance standard for buildings (SNI 1726-2013), and (3) standard of concrete for structural buildings (SNI 2847-2013). This building design is categorised as Building Risk IV, which has value factor virtue of earthquake (Ie) about 1.5 and located on the medium soil types. The Earthquake loads analysis of this building using the spectrum response. Based upon the seismic criteria, this building is included as Building Type D with high risk of seismic level. Therefore, the building design uses Special Moment Resisting Frame System (SMRFS) to reach the greater performance of column capacity upon the beam or Strong Column Weak Beam. These conditions require the beam-column joint should be well designed in order to avoid collapse when the beams are undergoing plastic hinge. The depth of the hard ground at the site of implementation is 4 m and 9 m, type of land included in the category of land under. The location is adjacent with the existing building, so for minimize the vibration of pile foundation erection used size (30 x 30) cm.